Implementasi Ajaran Tri Hita Karana Pada Mahasiswa Program Studi Pariwisata Budaya Hindu Di Masa Pandemi Covid-19 - Pradna Lagatama; Nyoman Danendra Putra (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
In 2020, there will be Covid-19 Virus or severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). In preventing the transmission of Covid-19 in Indonesia, the government urges to prevent the virus from spreading by always implementing health procedures. The impact of this virus causes learning activities to be limited by conducting online learning for both students and students. Students can study from home without coming to campus with only electronic devices and internet networks, they can attend lectures. This also applies to the State College of Hindu Religion, Mpu Kuturan Singaraja, especially for students of the Hindu Cultural Tourism Study Program doing online lectures. One of the teachings of Hinduism that has global implications is the concept of Tri Hita Karana which means three causes of welfare, namely Prahyangan, Pawongan, Palemahan. During online learning students always apply the concept of the Tri Hita Karana teaching which is a concept of harmony and balance which consists of three parts, namely Prahyangan by establishing a harmonious relationship between humans and the Creator (Ida Sang Hyang Widhi Wasa, God Almighty), Pawongan establishes harmony the relationship between humans and humans, and Palemahan establishes a harmonious relationship between humans and nature. Various ways can be done to realize the Tri Hita Karana concept, one of which is the implementation of the yajna which is sincerely carried out by students.Keywords : Implementation of the Tri Hita Karana teachings, Pandemic Time Covid-19